The Phenomenon of Dengue Fever in Climate Change - Cahyati, Widya Hary; Dina Nur Anggraini Ningrum; Andi Irwan Benardi; Hanif Pandu Suhito; Izha Fajar Al Isynaini; Ratna Sri Indrawati (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Dengue fever is a health challenge in tropical and subtropical countries. The increase in dengue cases in Indonesia is influented by urbanization, climate change, higher population mobility, and community behavior. This study aims to describe the climate factors, temperature, humidity, rainfall, and wind speed, as well as dengue fever cases. This study uses a descriptive observational design with an ecological study approach. The data collection technique used in this study was secondary data in the form of documentation studies by analyzing records of dengue fever case numbers and climate data. The average monthly temperature ranges from 26.8 to 31.3°C, the average monthly humidity ranges from 65.1 to 85.7%, and rainfall fluctuates significantly, with the highest intensity reaching 28.7 mm. Dengue fever cases show a fluctuating trend, with the highest number in 2023 at 541 cases. Climate factors play a role in the dynamics of dengue cases in Semarang City. Temperature and humidity are within the optimal range that supports mosquito breeding and dengue virus transmission. High rainfall allows for puddles of water to form, which serve as breeding grounds for mosquitoes. Low wind speeds also facilitate mosquito flight activity.